1998
DOI: 10.1002/(sici)1521-3773(19980803)37:13/14<1931::aid-anie1931>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Practical Access to 2-Alkylsuccinates through Asymmetric Catalytic Hydrogenation of Stobbe-Derived Itaconates

Abstract: Enantiomerically enriched 2-substituted succinic acid derivatives of general structure 2 have attracted great interest recently because of their utility as chiral building blocks and peptidomimetics in the design of pharmaceuticals, flavors and fragrances, and agrochemicals with improved properties. [1] Asymmetric catalytic hydrogenation of b-substituted itaconic acid derivatives (1) potentially offers one of the most convenient and practical routes to this class of compounds. No such catalyst system has yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 2 publications
4
70
1
Order By: Relevance
“…[1Ϫ5] Since DIOP was found to display high enantioselectivity in asymmetric hydrogenation catalyzed by rhodium complexes, it has been considered that C 2 -symmetrical bis(phosphane) ligands are endowed with superior catalytic properties. [6] A variety of C 2 -symmetrical ligands, such as DIPAMP, [7] BINAP, [8] DuPHOS, [9,10] BIPNOR, [11] and PennPHOS, [12] have indeed displayed superior asymmetric induction properties in an array of transition metal catalyzed reactions. On the other hand, it has also been shown that unsymmetrical bis(phosphane) ligands such as Josiphos, [13] Quinaphos, [14] Binaphos, [15] and others, [16,17] with different groups on the two phosphorus atoms, are effective for asymmetric hydrogenation in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…[1Ϫ5] Since DIOP was found to display high enantioselectivity in asymmetric hydrogenation catalyzed by rhodium complexes, it has been considered that C 2 -symmetrical bis(phosphane) ligands are endowed with superior catalytic properties. [6] A variety of C 2 -symmetrical ligands, such as DIPAMP, [7] BINAP, [8] DuPHOS, [9,10] BIPNOR, [11] and PennPHOS, [12] have indeed displayed superior asymmetric induction properties in an array of transition metal catalyzed reactions. On the other hand, it has also been shown that unsymmetrical bis(phosphane) ligands such as Josiphos, [13] Quinaphos, [14] Binaphos, [15] and others, [16,17] with different groups on the two phosphorus atoms, are effective for asymmetric hydrogenation in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…DuPhos has been shown to be useful for the preparation of a-amino acid derivatives [222,[226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241], including b-branched examples that are not accessible with DIPAMP [222,242,243]. The catalyst system is also successful with enamides, enol acetates, unsaturated carboxylic, and itaconic acids [7,115,222,[244][245][246][247][248][249][250].…”
Section: Duphosmentioning
confidence: 99%
“…This is demonstrated in the asymmetric hydrogenation of itaconic acid derivatives to give chiral succinates 17 (Fig. 11) [3]. This reaction is greatly accelerated by the presence of a sub-stoichiometric amount of base.…”
Section: Substrate Synthesis Purity and Catalyst Loadingmentioning
confidence: 99%
“…It is proposed that this facilitates the coordination of the resultant carboxylate group to the catalyst. A wide range of functionalities are tolerated as is the presence of E/Z isomers at the prochiral center [3]. On the contrary, itaconate derivatives with ester or amide functionalities on the b-carboxylate and the free a-carboxylic acid are not good substrates for rhodium DuPHOS catalysts, giving low conversion and selectivity.…”
Section: Substrate Synthesis Purity and Catalyst Loadingmentioning
confidence: 99%
See 1 more Smart Citation